PENGARUH VIDEO ANIMASI TERHADAP TINGKAT PENGETAHUAN MENSTRUAL HYGIENE PADA SISWI DI SEKOLAH DASAR MUHAMMADIYAH AMBARKETAWANG 3 SLEMAN: PENGARUH VIDEO ANIMASI TERHADAP TINGKAT PENGETAHUAN MENSTRUAL HYGIENE PADA SISWI DI SEKOLAH DASAR MUHAMMADIYAH AMBARKETAWANG 3 SLEMAN - Runa Danahu Angkotasan; Khristina Dias Utami; Sekar Dwi Safitri (HEALTHY BEHAVIOR JOURNAL, 2026)
Background : Adolescence is a crucial phase marked by reproductive maturity, shown through menstruation. However, poor menstrual hygiene practices remain common in Indonesia, leading to risks of reproductive tract infections. Objective : This problem is linked to limited knowledge, inadequate sanitation, and low social support. Health education using media such as animated videos is one effort to improve girls’ understanding, as this method is engaging and easier to comprehend, especially at the elementary school level. Methods :  This study used a quantitative approach with a pre-experiment one- group pre-test and post-test design. The population was 74 female students, and all of them were sampled using the total sampling technique. The data were collected through the instrument of a questionnaire. The study was conducted at SD Muhammadiyah Ambarketawang 3 Sleman, in February–March 2025. Data were then analysed using the Paired T-Test. Result :  Menstrual animation video has proven to have an effect on the increased comprehension of the students of SD Muhammadiyah Ambarketawang 3 Sleman. Therefore, the use of animated video media can be applied as an effective and engaging health education method to improve elementary school girls’ knowledge regarding menstrual hygiene. Conclusion : This educational approach may help schools and health workers provide reproductive health information more clearly, increase students’ awareness of proper menstrual hygiene practices, and support the prevention of reproductive tract infections among adolescents.